Multiple pathways to scaling up and sustainability: an exploration of digital health solutions in South Africa - Swartz, Alison; LeFevre, Amnesty E.; Perera, Shehani; Kinney, Mary V.; George, Asha S. (Globalization and health, 2021)
Background With the aim to support further understanding of scaling up and sustaining digital health, we explore digital health solutions that have or are anticipated to reach national scale in South Africa: the Perinatal Problem Identification Programme (PPIP) and Child Healthcare Problem Identification Programme (Child PIP) (mortality audit reporting and visualisation tools), MomConnect (a direct to consumer maternal messaging and feedback service) and CommCare (a community health worker data capture and decision-support application). Results A framework integrating complexity and scaling up processes was used to conceptually orient the study. Findings are presented by case in four domains: value proposition, actors, technology and organisational context. The scale and use of PPIP and Child PIP were driven by ‘champions’; clinicians who developed technically simple tools to digitise clinical audit data. Top-down political will at the national level drove the scaling of MomConnect, supported by ongoing financial and technical support from donors and technical partners. Donor preferences played a significant role in the selection of CommCare as the platform to digitise community health worker service information, with a focus on HIV and TB. A key driver of scale across cases is leadership that recognises and advocates for the value of the digital health solution. The technology need not be complex but must navigate the complexity of operating within an overburdened and fragmented South African health system. Inadequate and unsustained investment from donors and government, particularly in human resource capacity and robust monitioring and evaluation, continue to threaten the sustainability of digital health solutions. Conclusions There is no single pathway to achieving scale up or sustainability, and there will be successes and challenges regardless of the configuration of the domains of value proposition, technology, actors and organisational context. While scaling and sustaining digital solutions has its technological challenges, perhaps more complex are the idiosyncratic factors and nature of the relationships between actors involved. Scaling up and sustaining digital solutions need to account for the interplay of the various technical and social dimensions involved in supporting digital solutions to succeed, particularly in health systems that are themselves social and political dynamic systems.